Diarrhoea in adult cancer patients: ESMO clinical practice guidelines - Bossi, Paolo; Jordan, Karin (Annals of oncology, 2018)
Diarrhoea is defined as the frequent passage of loose stools with urgency (or more frequent passage than is normal for the individual). Objectively defined, it
Gesehen am 04.04.2019